Poetry therapy : theory and practice - Mazza, Nicholas (New York, NY : Routledge, 2022)
"The third edition of Poetry Therapy, written by a pioneer and leader in the field, updates the only integrated poetry therapy practice model with the most current literature (featuring over 100 new references) and practice experiences. Building on his definition of poetry therapy (the use of language, symbol, and story in therapeutic, educational, and community building capacities), Mazza continues to expand poetry therapy applications and techniques, carefully illustrating the use of poems, expressive writing, and symbolic activities for healing. New edition updates include new research findings and methods, especially with respect to writing/poetry and brain activity and address contemporary topics such the LGBTQ+ population, gender identity, disabilities, veterans, and nature are also addressed. New chapters on spirituality, the pandemic, and a personal account of poetry and running are also featured. This is a truly invaluable resource for any serious practitioner, educator, or researcher interested in poetry therapy, bibliotherapy, writing, and healing, or the broader area of creative/expressive arts therapies"--
Keywords: Poetry -- Therapeutic use; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health